KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS NEGOSIASI SISWA KELAS X SMA NEGERI 9 PADANG (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The objectives of this study are threefold as follows. (1) to describe the reading comprehension skills of class X students of SMA Negeri 9 Padang. (2) to describe the negotiation text writing skills of class X students of SMA Negeri 9 Padang. (3) to analyze the correlation between reading comprehension skills and negotiation text writing skills of class X students of SMA Negeri 9 Padang. This type of research is quantitative research with a correlational method. The research design used is a two-variable correlational relationship. The population of this study was 471 class X students of SMA Negeri 9 Padang. The sample in this study was 60 people. Sampling in this study used a proportional random sampling technique. The research instruments were tests, namely an objective test of reading comprehension skills and a performance test of negotiation text writing skills. The results of this study are threefold. First, the reading comprehension skills of class X students of SMA Negeri 9 Padang are at the more than sufficient qualification (LdC) with an average score (74.50). Second, the negotiation text writing skills of class X students of SMA Negeri 9 Padang are at the good qualification (B) with an average score (77.81). Third, there is a significant correlation between reading comprehension skills and negotiation text writing skills of class X students of SMA Negeri 9 Padang at n-1 degrees of freedom (60-1=59) and a significance level of 95%. H0 is rejected and H1 is accepted because t count is greater than t table, namely (t count 5.46> t table 1.67). In other words, the better the students reading comprehension skills, the better the students' negotiation text writing skills will be.